Analisis Ketersediaan Sarana Dan Prasarana Pendidikan Sekolah Dasar dalam Meningkatkan Mutu Pendidikan di SD Inpres Sarudu IV Sulawesi Barat - Ezri Gusti Arruan; I Gusti Ayu Purnamawati; Basilius Redan Werang (Pascasarjana Universitas Pendidikan Ganesha, 2023)
This study aims to describe what efforts have been made to overcome obstacles related to the provision of elementary education facilities and infrastructure in improving the quality of elementary school education at SD Inpress Sarudu IV, West Sulawesi. This research will be designed into qualitative research where research focuses on phenomena that occur in the field. This study uses a case study approach in observing the phenomena found. This study uses snowballing techniques in determining research subjects. Methods of data collection by observation, interviews, surveys and documentation. The data obtained were analyzed with Data Reduction, Data Display, Conclusion Drawing, the results of the study showed that the facilities and infrastructure of SD Inpress Sarudu IV West Sulawesi were well available. The facilities and infrastructure at SD Inpress Sarudu IV West Sulawesi are in accordance with the Regulation of the Minister of National Education of the Republic of Indonesia No. 24 of 2007 concerning Standards of Facilities and Infrastructure for Elementary Schools/Madrasah Ibtidaiyah (SD/MI), the condition of infrastructure is in good and adequate condition.